FACTORS RELATED TO DIARRHEA IN CHILDREN IN THE WORKING AREA OF PUSKESMAS PANCUR, 2020 - Sardianti Sardianti; Siska Natalia; Rizki Sari Utami (Jurnal Vokasi Keperawatan (JVK), 2021)
Diarrhea is one of the most common diseases affecting children around the world. Diarrhea is the loss of fluids and electrolytes by defecating in the form of watery or watery stools more than 3 times a day with or without blood or mucus (Sudarti, 2015). Diarrhea is included in the top 10 disease category in Lingga Regency. The number of diarrhea at all ages in 2018 was 1665 people, data was obtained from 10 health centers in Lingga Regency. From the data of the Pancur Puskesmas, the incidence of diarrhea in children 1-5 years old has increased to 15% from 112 toddlers to 124 toddlers in 2020. Thus, the researchers wanted to examine the factors associated with the incidence of diarrhea in children under five in the working area of the Pancur Community Health Center in 2020. The sample of the study was mothers of children aged 7-59 months who met the exclusion and inclusion criteria which amounted to a large sample taken by looking at The number of population exceeds 100 then the number of samples taken is 30% of the total population (30/100 x 124 = 37 people). The sampling method in this study was purposive sampling (Ari Saryano, 2014). There is a significant relationship between maternal knowledge about diarrhea and the incidence of diarrhea in children under five years of work at the Pancur Puskesmas Health Center which is marked by a value of p = 0.011 <? = 0.05 with X2 count = 9.024 There is a significant relationship between mothers' attitudes towards diarrhea and the incidence of diarrhea in children under five in the Work Area of the Pancur Puskesmas in 2020 which is marked by a value of p = 0.026 <? = 0.05 with X2 count = 4.937. It is hoped that health workers can educate mothers who have toddlers about personal hygiene for toddlers so that toddlers can avoid diarrhea.